Methodology for the preparation of a photographic historical information system for local history in Extremadura. The example of Los Santos de Maimona - Rubiano Montaño, Penélope; Vivas Moreno, Agustín; Nuño Moral, María Victoria (Revista General de Información y Documentación, 2019)
The purpose of this research is to establish a methodology for the creation of aPhotographic Documentary Information System (SIDF) that allows us to study local history. Themethodological resources used have been several: documentary techniques, which include theidentification of the image and its documentary description through the adaptation of archivalregulations, as well as the extraction of descriptors; information technologies, through the elaborationof a thesaurus that is inserted in an automated document manager, which is a tool that uses information and communication technologies to obtain more performance from the application; and,finally, the analytical methods, which are the analysis of images in all their aspects (formal, physicaland conceptual). It is offered as a result a documentary manager that integrates the aforementionedmethodological resources as support of works of the needed local history. All this is applied to thestudy of the trades of Los Santos de Maimona, a town in the province of Badajoz. Consequently, weconclude that the importance of photography as a documentary resource for the elaboration ofcollective memory requires SIDF as a procedure for searching and retrieving information.
Keywords: Photographic documentation; Photographic; Local history; Documentary information system